1989
DOI: 10.1007/bf01870791
|View full text |Cite
|
Sign up to set email alerts
|

Activation of K+ channels in renal medullary vesicles by cAMP-dependent protein kinase

Abstract: ADH, acting through cAMP, increases the potassium conductance of apical membranes of mouse medullary thick ascending limbs of Henle. The present studies tested whether exposure of renal medullary apical membranes in vitro to the catalytic subunit of cAMP-dependent protein kinase resulted in an increase in potassium conductance. Apical membrane vesicles prepared from rabbit outer renal medulla demonstrated bumetanide- and chloride-sensitive 22Na+ uptake and barium-sensitive, voltage-dependent 86Rb+ influx. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…In the case of bumetanide, both amiloride and forskolin inhibit this increase in K+ concentration and so could suggest that this is a ductal phenomenon. It is also possible that a change in intracellular pH or cyclic AMP concentration caused by amiloride and forskolin could inhibit apical K+ channels (Brown, Loo & Wright, 1988;Reeves, McDonald, Mehta & Andreoli, 1989). Clearly, it is not possible to reach a definitive conclusion regarding this phenomenon on the basis of present evidence.…”
Section: The Effects Of Bariumcontrasting
confidence: 49%
“…In the case of bumetanide, both amiloride and forskolin inhibit this increase in K+ concentration and so could suggest that this is a ductal phenomenon. It is also possible that a change in intracellular pH or cyclic AMP concentration caused by amiloride and forskolin could inhibit apical K+ channels (Brown, Loo & Wright, 1988;Reeves, McDonald, Mehta & Andreoli, 1989). Clearly, it is not possible to reach a definitive conclusion regarding this phenomenon on the basis of present evidence.…”
Section: The Effects Of Bariumcontrasting
confidence: 49%
“…The effect of vasopressin is mediated by a cAMP-dependent pathway because application of cAMP analogs mimics the effect of vasopressin (21). That vasopressin stimulates the apical K ϩ conductance in the TAL has been reported in several studies using microelectrodes and vesicles (23,24). ROMK channels have three putative serine PKA phosphorylation sites (2), and Xu et al (25) have shown that these sites can be phosphorylated in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, we have observed that, in apical medullary vesicles, the adenylate cyclase cascade produces a direct activation of K + channels [23]; and that, in intact mTALH segments, blockade of apical membrane Na + : K + : 2C1-entry with furosemide abolishes detectable ADH-dependent increases in basolateral C1-conductance [19]. Thus we have proposed that, in mTALH segments, ADH increases the rate of apical membrane salt entry, and that the attendant rise in basolateral C1-conductance is due to a rise in intracellular C1-activity [19].…”
Section: Introductionmentioning
confidence: 95%
“…22Na+ UPTAKE Bumetanide-sensitive, (K++C1-)-dependent 22Na+ uptake was determined in triplicate as described previously [23] after loading the vesicles with solution H. A 20 /xl-aliquot of vesicles was added to 25 ~*1 of solution I containing 0.9 mM =Na + (32/xC/ml), 1.8 mM amiloride, and either 0 or 1.8 mM bumetanide, This re- suited in a final outside solution containing 1 mM amiloride with or without 1 mM bumetanide (Solution J, Table 1), which has hypertonic relative to the inside solution. After 5 sec, 1.5 ml of a cold stop solution containing 150 mM KNO3 and 20 mM triethanolamine was added and the vesicles were filtered and then washed four times with 1.5 ml of the cold stop solution.…”
Section: C1 Uptakementioning
confidence: 99%